2020
DOI: 10.3390/nu12103139
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fatty Acids in Postprandial Triglyceride-Rich Lipoproteins Modulate Human Monocyte-Derived Dendritic Cell Maturation and Activation

Abstract: Dietary fatty acids have been demonstrated to modulate systemic inflammation and induce the postprandial inflammatory response of circulating immune cells. We hypothesized that postprandial triglyceride-rich lipoproteins (TRLs) may have acute effects on immunometabolic homeostasis by modulating dendritic cells (DCs), sentinels of the immunity that link innate and adaptive immune systems. In healthy volunteers, saturated fatty acid (SFA)-enriched meal raised serum levels of granulocyte/macrophage colony-stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Besides omega-3 fatty acids, a large number of other serum fatty acids may influence inflammatory processes. Saturated fatty acids were shown to significantly increase post-prandial dendritic cell circulation (as a sign of innate immunity) in healthy volunteers in contrast to omega-3 poly-unsaturated fatty acids 25 . In a study published in 2010, by Ramirez-Tortosa et al, the levels of a broader spectrum of fatty acids were analyzed with regard to periodontitis 26 .…”
Section: Introductionmentioning
confidence: 94%
“…Besides omega-3 fatty acids, a large number of other serum fatty acids may influence inflammatory processes. Saturated fatty acids were shown to significantly increase post-prandial dendritic cell circulation (as a sign of innate immunity) in healthy volunteers in contrast to omega-3 poly-unsaturated fatty acids 25 . In a study published in 2010, by Ramirez-Tortosa et al, the levels of a broader spectrum of fatty acids were analyzed with regard to periodontitis 26 .…”
Section: Introductionmentioning
confidence: 94%
“…[ 15 ] This mechanism would not be relevant, despite the role of macrophages and particularly dendritic cells as potent antigen presenting cells in adipose tissue, [ 51 ] as it has been demonstrated that HFDs enriched in MUFAs promote a surrounding lipid environment dominated by oleic acid and the prevalence of alternatively activated macrophages in eWAT [ 38 ] and that triglyceride‐rich lipoproteins isolated from volunteers after the ingestion of a high‐fat meal rich in olive oil impede maturation and pro‐inflammatory activation of monocyte‐derived dendritic cells. [ 52 ] In fact, the repression of the Elane gene in the visceral adipose depot may suggest that HFDs enriched in MUFAs did not induce the recruitment of neutrophils into eWAT. The lower cell death background in the spleen after HFDs enriched in MUFAs compared to HFD‐SFAs, which may be another proof of decreased inflammatory tone, [ 20 ] could have contributed to maintaining the survival of immune cells within this organ.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelium plays a role in preventing the formation and development of AS through platelet aggregation, vascular tension, coagulation, and fibrinolysis ( 39 ). The activation of white blood cells and oxidative stress produced by monodietary fat meal may lead to endothelial dysfunction and form the early stages of AS ( 40 , 41 ).…”
Section: The Related Mechanism Of Postprandial Lipemia-induced Atherosclerosismentioning
confidence: 99%
“…The instability of lipid metabolism and chronic postprandial inflammation are the underlying pathogenesis of AS-induced CVD ( 41 ). ApoB100-containing lipoproteins enter the arterial subendothelium and are retained by interaction with membrane proteoglycans through charge-based interactions and sphingolipases.…”
Section: The Related Mechanism Of Postprandial Lipemia-induced Atherosclerosismentioning
confidence: 99%